Psychometric Properties of Acceptance and Action Questionnaire (AAQ) for Weight-Related Difficulties Questionnaire among University Students - Patricia Pawa, Pitil; Siti Raudzah, Ghazali (Universal Publishers, 2021)
This study evaluates the 22-item of Acceptance and Action on Weight-Related Difficulties Questionnaire-Revised 18 (AAQW-R18), which assesses weight-related psychological flexibility in university students. A total of 120 university students from the Faculty of Sports Science and Recreation, UiTM, aged 18 – 24 years old with a mean BMI= 22.71 ± 4.44 kg/m2 (range 15.72 – 46.7kg/m2 ) participated in this study. Participants were 65% male and 35% female. The corrected item-total correlation found that four items (items 1, 7, 14 and 18) had to be omitted due to low and negative correlations. High internal consistency was found in full length and the new AAQW (AAQW-R18). The new AAQW showed with a good convergent validity property. A two-week test-retest reliability was excellent. Age, gender and BMI categories were similar in AAQW score distributions. The AAQW-R18 demonstrates a greater criterion-related and convergent validity, confirming the validity and reliability of this instrument to measure psychological flexibility assessment among university students. It is concluded that the AAQW-R18 can be used for measuring weight-related psychological flexibility among our population.